The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1103/physrevd.66.114013
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quark photoproduction in thek-factorization approach

Abstract: Abstract. We investigate the heavy quark photoproduction based on the k ⊥ -factorization approach, focusing on the results from the saturation model. The deviations in the results using the unintegrated gluon distribution considering the saturation model and the derivative of the collinear gluon distribution are analysed. Total cross sections and p T distributions are analysed in detail, setting the deviations between the color dipole approximation and the complete semihard approach.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 68 publications
4
23
0
Order By: Relevance
“…The results presented in Ref. [30] indicated that the contribution of the double diffractive reaction for the double J/Ψ production are similar to those derived in Ref. [31] considering the exclusive production.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The results presented in Ref. [30] indicated that the contribution of the double diffractive reaction for the double J/Ψ production are similar to those derived in Ref. [31] considering the exclusive production.…”
supporting
confidence: 79%
“…In particular, we will update the predictions derived in Ref. [30] considering a more recent parameterization for the diffractive gluon distribution, which was obtained in Ref. [32] by fitting the latest HERA data for diffractive ep reactions.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…(20), with a threshold factor (1 − x) n thres , taking n thres = 5 for a 3-flavor analysis and n thres = 7 for a 4-flavor one. This procedure ensures consistent description of heavy quark production at the fixed target data [38].…”
Section: Dipole-nucleus Cross Section In the Saturation Modelmentioning
confidence: 99%
“…energy, W γ A , in the heavy quark photoproduction case as x = 4m 2 Q /W 2 γ A , as in the collinear case. The cross section for the heavy-quark photoproduction process is given by the convolution of the unintegrated gluon function with the off-shell matrix elements [33,34,35,36]. Considering only the direct component of the photon we have that σ phot tot reads as [35],…”
Section: The K ⊥ -Factorization Formalismmentioning
confidence: 99%